Familial atypical parkinsonism with rare variant in VPS35 and FBXO7 genes: A case report. Issue 46 (November 2016) - Bartonikova, Tereza; Mensikova, Katerina; Mikulicova, Lenka; Vodicka, Radek; Vrtel, Radek; Godava, Marek; Vastik, Miroslav; Kaiserova, Michaela; Otruba, Pavel; Dolinova, Iva; Nevrly, Martin; Kanovsky, Petr
Abstract : Supplemental Digital Content is available in the text Abstract: Background: A higher prevalence of parkinsonism was recently identified in southeastern Moravia (Czech Republic). Further research confirmed 3 large pedigrees with familial autosomal-dominant parkinsonism spanning 5 generations. Methods: This case report concerns a patient belonging to one of these 3 pedigrees, in whom motor and oculomotor symptoms were accompanied by frontal-type dementia, who finally developed a clinical phenotype of progressive supranuclear palsy. Molecular genetic examinations were performed due to the positive family history. Results: No previously described causal mutation was found. After filtering against common variants (minor allele frequency (MAF) < 0.01), 2 noncoding and 1 synonymous rare mutation potentially associable with parkinsonism were identified: GIGYF2—GRB10 Interacting GYF Protein 2, PARK11 (c.∗2030G > A, rs115669549); VPS35 gene—vacuolar protein sorting 35, PARK17 (c.102 + 33G > A, rs192115886); and FBXO7 —F-box only protein 7 gene, PARK15 (c.540A > G, rs41311141). Conclusion: As to the changes in the FBXO7 and VPS35 genes (despite phylogenetic conservation in primates), probably neither the FBXO7 nor the VPS35 variants will be direct causal mutations. Both described variants, and possibly the influence of their combination, could increase the risk of the disease.